Enantioseparation and determination of asenapine in biological fluid micromatrices by HPLC with diode array detection. Issue 6 (12th January 2018) - Protti, Michele; Vignali, Alice; Sanchez Blanco, Teresa; Rudge, James; Bugamelli, Francesca; Ferranti, Anna; Mandrioli, Roberto; Mercolini, Laura
Abstract: Asenapine is a recent drug approved in the European Union for the treatment of bipolar disorder. An original approach has been developed for asenapine analysis in patients treated with the drug, including miniaturized microsampling procedures, separation and quantitation of drug enantiomers. An original enantioselective method based on high‐performance liquid chromatography with diode array detection was developed and applied to the determination of asenapine enantiomer levels in innovative haematic samples: four micromatrices have been tested, two based on dried matrix spots (dried blood spots and dried plasma spots) and two based on volumetric absorptive microsampling (from blood and plasma). Chiral separation was achieved on a cellulose‐tris(3, 5 dimethylphenylcarbamate) column, with a mobile phase containing bicarbonate buffer and acetonitrile. The method was validated with satisfactory results of linearity and precision on all matrices that showed also a significant performance in terms of stability, feasibility and reliability, when compared to fluid plasma sampling, handling and processing. Among micromatrices, both volumetric absorptive microsampling types were superior to dried matrix spots in terms of data reproducibility and correspondence with plasma levels. The bioanalytical approach proposed herein provides for the first time a chiral high‐performance liquid chromatographic method for the determination of asenapine enantiomers, coupled to a very effective microsampling strategy.